Enquadramentos jornalísticos do Governo Sartori: a seleção das fontes em Zero Hora - Rodrigues, Cristiano Magrini (2017)
This paper shows the political news coverage in print publications from the perspective of frameworks studies (frame analysis). The proposal is to understand about José Ivo Sartori’s government, in the Brazilian state of Rio Grande do Sul, through the mentions of journalistic sources in the newspaper Zero Hora. In order to offer a comprehension of this subject and to achieve the objective of the analysis, it seeks to understand the context and phases imbricated in the construction of news that eventually determine the frameworks arranged in the pages of the newspaper. This comprehension starts from a look at the Theories of Journalism. The aspects of reality highlighted by the frames in the press have a power of emphasis and exclusion. This is connected to the objective of understanding which the relations between sources and frameworks are. The power of the sources’ speech comes from their influence in the construction of these frames mediatically propagated. From the Bourdieu’s Field theory (2010; 1994; 1974), the specificities of the Journalistic Field and their relation with the Political Field are discussed. The understanding the logic of the Bourdieu’s Fields allows to comprehend the disputes about the symbolic capital in these spheres of society and the values from it that are distributed by the press. With the journalistic habitus, it discuss the specificities about the process of the news structuring from the ideas of scholars in the area, mainly from the point of view of the events, Agenda-setting theory, sources and specially the news framing. This work formulates the analysis with a methodology perspective from the frame analysis affiliated to the studies from Gamson and Lasch (1980) and Gamson and Modigliani (1989). The analysis method indicates 17 main frames about Sartori’s government. They are gathered in frame packages of which ones signatures are extracted that indicate the core frames that make up each package. The signatures identified in this paper show the organization of the frames in a polarized way, with predominance of contestation frames versus reinforcement frames of the government. The first group is composed mostly by independent sources linked to trade union representation of civil servants. Opposite them, it’s possible to see mostly the official sources (government sources) and on a smaller occurrence, independent sources linked to business entities. The negative perspective or contestation perspective suggests that the government prejudice the society and the public services; has an aggressive attitude with the civil servants; acts in a demagogically and inconsistent way; is slow in making decisions and beyond that, is displeased, doesn’t communicate well and promotes a sense of chaos in society. The positive perspective said that the government is prudent, strategist and focused on efficiency and strives to fulfill their obligations; doesn’t prejudices the society, only have a realist and clear resolutions. Beyond the frames, there is an indication of the main groups of sources that fight for symbolic power of Politic Field in the Journalistic Field: government sources and trade unionists sources. The main frames forged in the complex flow that runs from the events until the publication is also shows in a graphic based on Charaudeau (2015a) that summarize the position of the sources and other actors in these process. These frameworks originated from 1013 citations, which of 560 highlighted to compose the analysis. At end, it’s understood that the sources contribution in the 17 main packages that synthesizes the frameworks of the year are linked to the Bourdieu’s theory with the strengthening of working rules of the Journalistic Field.